Văn học Việt Nam thế kỷ XX : Truyện ngắn 1945-1975. Q.2, T.5 - Phan Cự Đệ; Bùi Việt Thắng; Hà Văn Đức; Lý Hoài Thu; Hồ Thu Giang; Nguyễn Thị Hương Giang (Hà Nội : Văn học, 2004)
Vũ Bằng; Ngô Ngọc Bội; Triệu Bôn; Nguyễn Văn Bổng; Xuân Cang; Nam Cao; Đỗ Chu.
Keywords: Văn học Việt; Truyện ngắn Việt, -- 1945-1975.